Extensive ablation strategy for persistent atrial fibrillation impairs left atrial function but reduces recurrence rate. (3rd October 2022) - Oka, T; Koyama, Y; Inoue, K; Tanaka, N; Tanaka, K; Hirao, Y; Okada, M; Okamura, A; Iwakura, K; Fujii, K; Masuda, M; Watanabe, T; et al.
Abstract: Background: In catheter ablation for persistent atrial fibrillation (AF), extensive ablation strategy, such as linear ablation and/or complex fractionated atrial electrogram (CFAE) ablation in addition to pulmonary vein isolation (PVI-plus), might impair left atrial function more severely than PVI-alone strategy. Purpose: The aim of this study is to investigate the impact of extensive ablation strategy on LA function and assess the relationship between post-ablation LA function and recurrence. Methods: This study is a post-hoc subanalysis of the EARNEST-PVI randomized controlled trial, which investigated the efficacy of the PVI-alone strategy in comparison with PVI-plus strategy for persistent AF. From the 497 participants of EARNEST-PVI trial, we enrolled 191 patients with full datasets of pre- and post-ablation cardiac computed tomography (CT) at our Hospital. Patients were divided into PVI-alone and PVI-plus groups. Within one month before and 3 months after ablation, LA volume index (LAVI) and LA emptying fraction (LAEF) were calculated by using the Comprehensive Cardiac Analysis software on the Extended Brilliance Workspace. We assessed i) post-ablation LA function, ii) AF/atrial tachycardia (AT) -free rate after single and final session, and iii) relationship between post-ablation LAEF and ablation success in each group. Results: The indices of baseline LA remodeling were not different between PVI-alone (N=96) and PVI-plus groups (N=95) [LAVI: 71.4 (57.8, 82.0) vs. 68.7 (61.0, 78.1), P=0.92, LAEF: 13.7 (10.0, 17.4) vs. 13.0 (10.0, 16.9), PVI-alone vs. PVI-plus, P=0.78]. In overall patients, post-ablation LAEF did not differ among them [34.4 (26.1, 40.7) vs. 31.6 (26.0, 37.4), P=0.13]. In the analysis of patients showing sinus rhythm during the CT study, LAEF was significantly higher in PVI-alone (N=87) than in PVI-plus group (N=93) [35.7 (29.0, 41.0) vs. 31.7 (26.1, 37.5), P=0.011] (Figure 1A). AF/AT-free survival rate during median follow-up of 44 months was not different after first session (63.5% vs. 68.4%, P=0.33), while PVI-plus had a tendency towards higher success rate after final session (72.9% vs. 84.2%, P=0.053) (Figure 2). In receiver operating characteristics analysis for recurrence after first session, post-ablation decreased LAEF had significantly related to recurrence after PVI-alone (AUC: 0.733, P<0.0001), but not after PVI-plus (AUC: 0.567, P=0.31) (Figure 1B, C). Conclusion: Compared with PVI-alone strategy, PVI-plus strategy damaged LA function more severely, but tended to be related to higher success rate. Post-ablation LA function was related to recurrence in PVI-alone, but not in PVI-plus. Extensive ablation might have additional anti-arrhythmic effect regardless of iatrogenic myocardial damage. Myocardial injury by extensive ablation may less attribute to recurrence than intrinsic damage of LA. Funding Acknowledgement: Type of funding sources: None.